FACTORS AFFECTING COPING STRATEGIES FOR HEALTH WORKERS IN DEALING STIGMA DUE TO COVID-19 - Ana Zakiyah; Ika Ainur Rofi’ah (Bina Sehat Press. Departement Research and Community Engagement Bina Sehat PPNI Institute of Health Science, Indonesia, 2021)
Coping strategies used by health workers in dealing with community stigma due to Covid-19 are varied. The influencing factors include individual characteristics such as gender, marital status, profession, education level, marital status, salary, sift and others. The purpose of this study was to determine the factors that influence health workers in the selection of coping strategies. The design of this study was cross-sectional. The population is health workers who work in health services in Indonesia with a total of 530 samples through incidental sampling technique. The research instrument used a Brief Cope Inventory which consists of 28 question items with 14 subscale items. Data analysis used univariate, bivariate and multivariate. The coefficient of determination obtained is 0.125, meaning that the variability of the dependent variable that can be explained by independent variability is 12.5% ​​or about 87.5% the rest is explained by other factors outside the model, which means that it cannot be explained by the model including physical health factors and psychology.